The effects of physical activity on metabolic health, body composition and quality of life in patients with hypothyroidism: a narartive review - Ciurej, Aleksandra; Krajewska, Natasza; Dzieciol, Julia; Zylinska, Apolonia (Quality in Sport, 2026)
Background. Hypothyroidism, including Hashimoto's thyroiditis, is characterized by metabolic slowing, altered body composition, and persistent fatigue, which frequently undermine patient wellness even after biochemical euthyroidism is obtained with optimal levothyroxine therapy. Aim. To evaluate the evidence regarding the role of physical activity, specifically aerobic, resistance, and combined training, on metabolic health, body composition, and quality of life (QoL) in patientswith clinical and subclinical hypothyroidism. Material and methods. A thorough narrative review of the literature was performed using PubMed, focusing on randomized controlled trials, cohort studies, and cross-sectional analyses publishedpredominantly over the last decade. Variables analyzed included thyroid function tests, lipid profiles, anthropometric markers, and psychometric QoL assessments. Results. Current empirical evidence demonstrates that physical activity significantly improves physical and mental QoL components among patients with hypothyroidism. Recreational exercise improvessystemic thyroid function profiles and may enhance levothyroxine absorption. While standard pharmacological treatment primarily reduces water weight, structured exercise is required for meaningfulshifts in fat mass and to mitigate metabolic syndrome risks. Combined aerobic and resistance training yields the greatest improvements in mental health scores and TSH normalization. Conclusions. Physical activity acts as a useful adjunctive therapy in managing hypothyroidism. Structured exercise safely lessens the myopathic and metabolic detriments of the disease, potentiallyimproving functional capacity and QoL.